Analysis of business model and growth of an early-stage company in the e-learning market - Prouza, Kamil (2017)
The aim of this thesis is to analyze a business model of an e-learning company in the Czech Republic whose growth has been rather stagnant and identify ways to accelerate it. An analysis of the business model has been made base on the information provided by the owner. Also, a research of current and prospective customers was conducted using a questionnaire distributed through an online tool. The sample for the current customers consisted of all current customer while the sample for prospective customers consisted of 1 473 contacts in production and manufacturing companies. Based on the results, a set of recommendations have been made for the company. The recommendations, if followed, should accelerate the growth and enable the company to become an important player in the e-learning market.